Tomada de decisão em sistema de transporte urbano: uma análise multicritério - (:unkn) unknown (Universidade Federal do Amazonas, 2012)
In Brazil, most of the population lives in cities and urban centers and large part of Brazil urbanization took place quickly and without planning. The accelerated rural-urban migration contributed even more for cities acquire the image of urban populous and disorganized. The result of this training process is also reflected in the organization of various public services essential for the development of cities, among which stands out the public transportation. The problems regarding this service have generated large waste as the waiting time, travel costs, pollution, accidents and others, which tend to deteriorate, negatively impacting both the productivity of urban space and the quality of life. Aiming at a rapid reorganization of public transportation, the search for alternatives is growing more efficient and tailored to local economic realities and possibilities, aimed not only meet current needs but also future. To achieve its objectives, this paper draws on research literature and documents to justify the foundations of city planning and urban growth thereof, describing the whole process of development and also about addressing the reality of public transport in Manaus and the need to implement a new system, using a model decision. Therefore, this research aims to present the applicability of multicriteria methods through comparative analysis between public transports systems as an aid to the decision maker in choosing the alternative considered most satisfactory. It also aims to identify the main public transport systems adopted in Brazil, in addition to analyzing the current situation of public transport in the city of Manaus. It is further objective of this research relate to decision making and on multicriteria methods, more specifically the method Promethée II, as a tool to aid in decision making about the new system of public transportation that should be adopted by Manaus. After application of the method Promethée II based on the criteria and weights set by the managing agency of public transport in the capital of Amazonas, the research indicated that the transport system is the most satisfactory alternative to meet the needs of Manaus and respond to issues raised in this paper
Keywords: Decisão; Método promethée II; Sistema de transporte coletivo; Decision; Method promethée II; public transport system; ENGENHARIAS: ENGENHARIA DE PRODUÇÃO